SEJARAH JOGET "DANGKONG" PADA MASYARAKAT MORO KABUPATEN KARIMUN - Zurika Mitra; Kamaruddin '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to find out (1)history of Joget Dangkong in Moro society Karimun Regency (2) the form of movement, musical instruments, songs, players, clothing and makeup of Joget in Moro’s district (3) the conditions of Joget Dangkong at the present time in Moro Karimun Regency (4) the society and Governmen’s effort in preserving Joget dangkong. (5) the factors that inhibit society and Government in preserving the art of Joget Dangkong. The use of this research (1) to give the information about Joget Dangkong for the society and those who need it (2) to develop the writer’s knowledge about the history of the art of Joget Dangkong in Moro society, Karimun Regency (3) as a research information for those who need in the future (4) as the University’s contribution for the world of education for the better period. The methods that is used in this research is descriptive qualitatif. The research location is in the Moro Region, Karimun Regency. The results of this reasearch indicate that of art Joget Dangkong derived from the district of Moro Karimun Regency. Before its develop among the society, Joget Dangkong is presented for the kingdom that were in Malay. In 1913 the arts of Joget Dangkong develop among the society in Moro. Now, the existence of the art of Joget Dangkong still being preserved by the society and the Government.Key Words : History, Joget Dangkong